A case of ventricular fibrillation as a consequence of capecitabine-induced secondary QT prolongation: A case report. Issue 1 (July 2017) - Hayasaka, Kazuto; Takigawa, Masateru; Takahashi, Atsushi; Kuwahara, Taishi; Okubo, Kenji; Tanaka, Yasuaki; Misawa, Toru; Mizusawa, Masafumi; Yamakami, Yosuke; Kojima, Keisuke; Sagawa, Yuichiro; Hishikari, Keiichi; et al.
Abstract: Capecitabine is an oral fluoropyrimidine which can prolong QT interval. However, there have been no reports that capecitabine induced ventricular fibrillation (VF) due to secondary QT prolongation in patients with no structural heart disease. A 39-year-old woman developed VF during the chemotherapy of capecitabine for colon cancer. At the administration, corrected QT interval (QTc) was prolonged to 559 ms despite no evidence of organic heart disease. Discontinuation of capecitabline normalized the QTc (414 ms). During the follow-up of eight years, neither the QTc prolongation nor the recurrent VF has been detected. We report the rare case of capecitabine-related VF without any organic heart disease. <Learning objective: Capecitabine is an oral fluoropyrimidine carbamate commonly used to treat colorectal and breast cancer. Capecitabine has been reported to be associated with VF due to vasospasm. However, capecitabine is also associated with QT elongation. This is the first report to describe VF due to capecitabine-related secondary long QT syndrome in a patient with no cardiac heart disease. Physicians must carefully follow up patients during capecitabine chemotherapy with serial electrocardiograms.>